The struggle for organisational change: how the ActionAid Accountabili ty, Learning and Planning System emerged - Scott-Villiers, Patta (Policy & Practice, 2002)
Change is driven not only by good ideas, but also by disagreement and frustration. This article takes the reader through a selective organis ational history of the British NGO ActionAid from 1998 to 2001, lookin g at events and changes that had a bearing on the